Changes in distribution, morphology and ultrastructure of chloride cell in Atlantic salmon during an AGD infection. Issue 10 (20th August 2019) - Chang, Yao‐Chung; Hamlin‐Wright, Harry; Monaghan, Sean; Herath, Tharangani; Baily, Johanna; del Pozo, Jorge; Downes, Jamie; Preston, Andrew; Chalmers, Lynn; Jayasuriya, Nilantha; Bron, James E.; Adams, Alexandra; et al.
Abstract: Amoebic gill disease (AGD) is emerging as one of the most significant health challenges affecting farmed Atlantic salmon in the marine environment. It is caused by the amphizoic amoeba Neoparamoeba perurans, with infestation of gills causing severe hyperplastic lesions, compromising overall gill integrity and function. This study used histology, transmission electron microscopy (TEM), immunohistochemistry and transcript expression to relate AGD‐associated pathological changes to changes in the morphology and distribution of chloride cells (CCs) in the gills of Atlantic salmon ( Salmo salar L.) showing the progression of an AGD infection. A marked reduction in numbers of immunolabelled CCs was detected, and a changing pattern in distribution and morphology was closely linked with the level of basal epithelial hyperplasia in the gill. In addition, acute degenerative ultrastructural changes to CCs at the lesion site were observed with TEM. These findings were supported by the early‐onset downregulation of Na + /K + ‐ATPase transcript expression. This study provides supportive evidence that histological AGD lesion assessment was a good qualitative tool for AGD scoring and corresponded well with qPCR genomic Paramoeba perurans quantification. Ultrastructural changes induced in salmon CCs as a result of AGD are reported here for the first time.